Utilization of Library Resources and Services of King’s College of the Philippines Junior High School - Molito, Violy (Journal of Interdisciplinary Perspectives, 2025)
While providing services to high school students, the challenges they face in using library resources and services include a lack of library resources and current books, insufficient knowledge of using library materials, and unawareness of library services, such as borrowing books. Furthermore, some students report that library hours are inadequate. Therefore, this study aimed to examine the utilization of library resources and services at KCP Junior High School. This study aimed to explore the utilization of library resources and services at KCP Junior High School, specifically analyzing the use of the library, level of familiarity, and problems encountered by junior high school students at King’s College of the Philippines. It also sought to identify significant differences between higher and lower grade levels in the use of library resources and services and in the level of familiarity with existing library resources and services. The study employed a quantitative research design, using a questionnaire administered to 161 junior high school students. The T-test was used as the statistical tool to determine the utilization of library resources and services. Results show that junior high school students often utilized the library for academic, personal development, and entertainment/leisure purposes, with an overall mean utilization score of 3.45. They were also familiar with the existing library resources and services, indicated by an overall mean familiarity score of 3.89. Despite this familiarity, various problems were encountered when using the library's resources and services. It is found that there is a significant difference between higher- and lower-grade levels in the use of library resources. Lastly, it was found that there is a substantial difference in the utilization of library resources between higher and lower grade levels, t(159) = 2.15, p = .033. However, there was no significant difference in the use of library services between these grade levels, t(159) = 0.86, p = .398.